PSYCHOLOGICAL AMORTIZATION FACTORS FOR MEDIA IMPACT IN DEVELOPMENT OF CHILDREN FROM DIFFERENT SOCIAL GROUPS - Olga I. Makhovskaya; Fyodor O. Marchenko (Russian State Vocational Pedagogical University, 2016)
The aim of this publication is to analyze the domestic and foreign psychological researches on influence of TV-programs on social, cognitive and emotional development of children. Methods. Methods involve a comparative historical and psychological analysis of papers, manuscripts and archival records of television companies. Results. The present study demonstrates that educational television, subsequently on-line resources for children, affect operative cognitive functions, increase cognitive motivation, and contribute to the formation of other important cognitive and social skills. However, the impact on children on-screen resources depends on the status and education level of the family. Scientific novelty. Much attention is given to the fact that it is the first attempt to provide historical and psychological analysis of world-wide studies of the effects of children's television, from the main countries-producers of TV and video programs for children of different age - Russia, USA, Germany, France, Israel, etc. Criteria and matrix for comparison of heterogeneous researches, the domestic theory of child development, cultural-historical approach, the theory of stage formation of mental actions, activity theory had been chosen. Practical significance of the research is that these criteria can be used to assess any of the videos, their educational potential. Psychologists involved in the process of television production, this article will help to simulate the learning process taking into account the age of the children and their socio-cultural origin.